Histological and radioisotopical analysis of the skull graft: An experimental study in rabbits - Parro, F. H.S.; Viterbo, F.; Viterbo, B. G.; Ueda, A.; Pinca, F. [UNESP]; Zanini, S. A. (Wolters Kluwer, 1992)
The purpose of this study was to develop an experimental model in rabbits that would permit us to analyze skull reconstruction and enable the study of bone autografts, osteofacial flaps, and other materials. We use the rabbit model to study the early integration of the skull autograft and to demonstrate the relationship between radioisotopical and histological analyses. © 1992 Mutaz B. Habal, MD.
Keywords: Histological analysis; Rabbit experimental model; Radioisotopical analysis; Skull bone graft